Experimental Studies and Finite Element Modeling of Piles and Pile Groups in Dry Sand under Harmonic Excitation (Journal of Engineering, 2014)
Foundations supporting reciprocating engines, radar towers, turbines, large electric motors, and generators, etc. are subject to vibrations caused by unbalanced machine forces as well as the static weight of the machine. If these vibrations are excessive, they may damage the machine or cause it not to function properly. In the case of block foundation, if changes in size and mass of the foundation do not lead to a satisfactory design, a pile foundation may be used. In this study, the dynamic response of piles and pile Groups in dry sand is investigated experimentally. The analysis involves the displacement response under harmonic excitation. In addition, a numerical modeling by using finite element method with a three-dimensional formulation is adopted to simulate the experimental model. The results of the numerical model showed that a good agreement is achieved between the predicted dynamic response and that measured from the experimental model.